1988
DOI: 10.1111/j.1467-9310.1988.tb00592.x
|View full text |Cite
|
Sign up to set email alerts
|

Information technology impacts on innovation

Abstract: In this paper, we propose a model of Information Technology (IT) impacts on innovation. We do not intend to generalize a specific model of innovation. Rather, the objective here is to explain how IT can facilitate innovation in a work group. Review of literature suggests that innovative ability of a work group is dependent on the capabilities of the individuals/group, the structure of the work group or organization, and the group/organizational environments. To explore this conceptual model, data were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…The empirical data also showed that the impact of demand pull on innovation was significant, while the impact of technology push was not. (Lee & Treacy, 1988;p. 270) To a certain degree, the problem with technology-push may be definitional.…”
Section: M P L I C At I O N S a N D Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The empirical data also showed that the impact of demand pull on innovation was significant, while the impact of technology push was not. (Lee & Treacy, 1988;p. 270) To a certain degree, the problem with technology-push may be definitional.…”
Section: M P L I C At I O N S a N D Discussionmentioning
confidence: 99%
“…From a practical standpoint, the notions of technology-push and technology transfer seem to be restricted to the influence of communication and information (cf. Lee & Treacy, 1988).…”
Section: M P L I C At I O N S a N D Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In their article Lee and Treacy (1988) have shown that an unstable environment generates increased potential for innovation. But it requires an organization intent on being up-dated and well-informed about changes in the environment.…”
Section: Mew Scanning Institutionsmentioning
confidence: 97%
“…A more advanced stream of literature, more in line with evolutionary economics, attempts to depict the value of particular subcomponents of IT [6,27,102,144]. For example, [144] used a multi-theoretic lens to argue that IT investments and capabilities influenced firm performance through three significant organizational capabilities (agility, digital-options and entrepreneurial-alert) and strategic processes (capabilitybuilding, entrepreneurial action and co-evolutionary adaptation).…”
Section: Literature On the Value Of Itmentioning
confidence: 99%